DEVELOPMENT OF A SOFTWARE BASED SYSTEM TO APPLY TURKISH BUILDING ENERGY PERFORMANCE DIRECTIVE - Akdogan, Kurtulus Erinc; Ustaoglu, Demiray; Akoglu, Kemal; Fil, Can; Tastan, Tolga; Harputlugil, Gulsu Ulukavak (MATTER: International Journal of Science and Technology, 2016)
This work is about the software named BEP-TR (Building Energy Performance -Turkey), which is developed upon request from Turkish Ministry of Environment and Urbanization to apply to build energy performance directive nationwide to improve the energy efficiency of buildings in Turkey. The directive requires that each building in the country must have an energy performance certificate (EPC) indicating the ratings of energy consumption and greenhouse gas (GHG) emission of the related building. BEP-TR software is designed mainly to issue EPC for buildings considering each phase of EPC preparation process and tasks of associated institutions and individuals. BEP-TR is mainly composed of two software applications called BEP-BUY and BEP-IS. BEP-BUY is a desktop application, which allows the user to design a building stored in XML project file and calculate its energy consumption and greenhouse gas emission to determine its corresponding ratings. EPC application for the designed building, which meets standards required by government is done by sending the project file of the building through BEP-BUY to the BEP-IS. BEP-IS is an internet based software which is under the control of the ministry. BEP-IS confirms the calculations made for the building using the received project file and initiates the process of preparing EPC. BEP-IS provides users who take part in this process interfaces designed as web pages. Users and their authorizations are managed by fully authorized users defined for the ministry through BEP-IS. Besides BEP-IS stores and reports data related to processes and users. There are two other modules called library and calculation which are embedded in both BEP-BUY and BEP-IS. Library module stores the data related to structural materials, which are determined to be usable in building construction. Calculation module contains the national calculation method developed to calculate greenhouse emission and energy consumption of a building using properties of materials selected from library module. In this study, as an example, a building is designed and its energy consumption is calculated using BEP-BUY.